Development of socio-affective capacities and their relationship with the pro-environmental behavior of the children of the initial educational institution No. 068 of the El Agustino district - Solis Mendoza, July Jacinta (2021)
The present research work had as its origin the bibliographic collection, in addition to the antecedents and experiences acquired during the year of intense work with students of basic training; At work he specialized in the search for work such as incorporating the environmental approach in the initial education of children, delimiting the variables of the development of socio-affective capacities and Pro[1]Environmental behaviors. The objective of the research was to determine the relationship between the Development of Socio-affective Capacities and Pro[1]Environmental Behavior in children of the Initial Educational Institution No. 068 of the El Agustino District, Lima in 2019. The present scientific work was carried out in A quantitative research framework with a correlational descriptive research design was considered as a sample for the application of the observation cards were 73 students of initial education of the EI. study. To collect the information, two observation sheets were used as instruments that were validated with the criteria of three highly prestigious expert judges, determining high levels of reliability; Cronbach's alpha shows a high level of reliability of the instruments. The data set was processed and analyzed at a descriptive level for the variables and dimensions, for the hypothesis test using the Pearson coefficient. The results of the study show that there is a direct and significantly significant relationship, both qualitatively and quantitatively, between the Development of Socio-affective Capacities and Pro[1]Environmental Behavior. This relationship was corroborated by the Pearson coefficient with a value of 0.968, an adjustment level of 93.6% and a Chi Square association of 0.00 as a bilateral coefficient of variation.